PENGARUH ROTASI JABATAN DAN REWARD SISTEM TERHADAP LOYALITAS PEGAWAI DENGAN DIMEDIASI OLEH MOTIVASI KERJA STUDI PADA KEJAKSAAN TINGGI KEPULAUAN RIAU - Andriansyah Andriansyah; Susi Hendriani; Machasin Machasin (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine and analyze the effect of job rotation and reward system on employee motivation. To find out and analyze the effect of job rotation and reward system on employee loyalty. To find out and analyze the effect of work motivation on employee loyalty. This study aims to determine and analyze the effect of work motivation mediating job rotation and reward systems on employee loyalty at the Riau Islands High Court. The population in this study were employees of the Riau Islands High Court. The sample in this study was 69 people. Analysis of the data used in this study is Structural Equation Modeling (SEM) AMOS. The results of the research conducted show that job rotation has a significant effect on work motivation. Reward has a significant effect on work motivation. Job rotation has a significant effect on employee loyalty. Reward has a significant effect on employee loyalty. Motivation has a significant effect on employee loyalty. Job rotation has a significant effect on employee loyalty through motivation. And Reward has a significant effect on employee loyalty through motivation.